Peluang dan Tantangan Transformasi Digital UMKM di Indonesia Pasca Pandemi COVID-19 - Zahiroh, Mun Yah (CV. Civiliza Publishing, 2022)
The purpose of this study is to analyze digital transformation strategies for MSMEs in Indonesia after the Covid-19 pandemic. The research method in this article is descriptive qualitative with content analysis. Analysis of opportunities and challenges is carried out from the side; 1) Economics; 2) Social, cultural, and demographic; 3) Politics, government, and law; 4) technology; and 5) competitive competitiveness. From the analysis of opportunities and challenges, strategies can be formulated: 1) technology adoption training for MSMEs must continue to be carried out; 2) MSMEs must follow online marketing trends such as Tiktok; 3) Information literacy of government assistance programs to MSMEs and digital literacy must be increasingly socialized; 4) MSMEs must begin to enter Global E-Commerce which is widely used by the global community accompanied by improvements in product quality according to export standards. Tujuan dari penelitian ini adalah untuk menganalisis strategi transformasi digital pada UMKM di Indonesia pasca pandemic Covid-19. Metode penelitian pada artikel ini adalah kualitatif deskriptif dengan analisis konten. Analisis peluang dan tantangan dilakukan dari sisi ; 1) Ekonomi; 2) Sosial, budaya dan demografi; 3) Politik, pemerintahan, dan hukum; 4) teknologi; dan 5) daya saing kompetitif. Dari analisis peluang dan tantangan dapat dirumuskan strategi : 1) pelatihan adopsi teknologi pada UMKM harus terus dilakukan; 2) UMKM harus mengikuti tren pemasaran online misalnya Tiktok; 3) Literasi informasi program bantuan pemerintah kepada UMKM dan literasi digital harus semakin disosialisakan; 4) UMKM harus mulai memasuki Global E-Commerce yang banyak digunakan masyarakat global yang diiringi dengan perbaikan kualitas produk sesuai standar ekspor.